Vpx overcomes a SAMHD1-independent block to HIV reverse transcription that is specific to resting CD4 T cells - Baldauf, Hanna-Mari; Ambiel, Ina; Trotard, Maud; Pan, Xiaoyu; Abraham, Libin; Fackler, Oliver Till (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Early after entry into monocytes, macrophages, dendritic cells, and resting CD4 T cells, HIV encounters a block, limiting reverse transcription (RT) of the incoming viral RNA genome. In this context, dNTP triphosphohydrolase SAM domain and HD domain-containing protein 1 (SAMHD1) has been identified as a restriction factor, lowering the concentration of dNTP substrates to limit RT. The accessory lentiviral protein X (Vpx) proteins from the major simian immunodeficiency virus of rhesus macaque, sooty mangabey, and HIV-2 (SIVsmm/SIVmac/HIV-2) lineage packaged into virions target SAMHD1 for proteasomal degradation, increase intracellular dNTP pools, and facilitate HIV cDNA synthesis. We find that virion-packaged Vpx proteins from a second SIV lineage, SIV of red-capped mangabeys or mandrills (SIVrcm/mnd-2), increased HIV infection in resting CD4 T cells, but not in macrophages, and, unexpectedly, acted in the absence of SAMHD1 degradation, dNTP pool elevation, or changes in SAMHD1 phosphorylation. Vpx rcm/mnd-2 virion incorporation resulted in a dramatic increase of HIV-1 RT intermediates and viral cDNA in infected resting CD4 T cells. These analyses also revealed a barrier limiting HIV-1 infection of resting CD4 T cells at the level of nuclear import. Single amino acid changes in the SAMHD1-degrading Vpx mac239 allowed it to enhance early postentry steps in a Vpx rcm/mnd-2-like fashion. Moreover, Vpx enhanced HIV-1 infection of SAMHD1-deficient resting CD4 T cells of a patient with Aicardi-Goutières syndrome. These results indicate that Vpx, in addition to SAMHD1, overcomes a previously unappreciated restriction for lentiviruses at the level of RT that acts independently of dNTP concentrations and is specific to resting CD4 T cells. Author Information: Hanna-Mari Baldaufa,b,c, Lena Stegmanna, Sarah-Marie Schwarza, Ina Ambiela,d, Maud Trotardd, Margarethe Martina, Manja Burggrafe, Gina M. Lenzif, Helena Lejkb,c, Xiaoyu Pand, Oliver I. Fregosog,1, Efrem S. Limg, Libin Abrahamd, Laura A. Nguyenf, Frank Rutschh, Renate Könige,i,j, Baek Kimf, Michael Emermang, Oliver T. Facklerd,k,2, and Oliver T. Kepplera,b,c,l,2aInstitute of Medical Virology, University Hospital Frankfurt, 60596 Frankfurt, Germany;bMax von Pettenkofer-Institute, Department of Virology, Ludwig Maximilians University, 80336 Munich, Germany;cInstitute of Virology, Technische Universität München/Helmholtz Zentrum, 81675 Munich, Germany;dCenter for Infectious Diseases, Integrative Virology, University Hospital Heidelberg, 69120 Heidelberg, Germany;eHost-Pathogen Interactions, Paul Ehrlich Institute, 63225 Langen, Germany;fCenter for Drug Discovery, Department of Pediatrics, Emory Center for AIDS Research, Emory University, Children’s Healthcare of Atlanta, Atlanta, GA 30322;gFred Hutchinson Cancer Research Center, Seattle, WA 98109;hDepartment of General Pediatrics, Münster University Children’s Hospital, 48149 Munster, Germany;iImmunity and Pathogenesis Program, Sanford Burnham Prebys Medical Discovery Institute, La Jolla, CA 92037;jGerman Center for Infection Research (DZIF), Langen, Germany;kGerman Center for Infection Research (DZIF), Heidelberg, Germany;lGerman Center for Infection Research (DZIF), Munich, GermanyEdited by Stephen P. Goff, Columbia University Medical Center, New York, NY, and approved January 25, 2017 (received for review August 16, 2016), Footnotes↵1Present address: University of California, Los Angeles, CA 90095.↵2To whom correspondence may be addressed. Email: oliver.facklermed.uni-heidelberg.de or Keppler@mvp.uni-muenchen.de.Author contributions: H.-M.B., R.K., O.T.F., and O.T.K. designed research; H.-M.B., L.S., S.-M.S., I.A., M.T., M.M., M.B., G.M.L., H.L., X.P., L.A., and L.A.N. performed research; O.I.F., E.S.L., F.R., R.K., B.K., and M.E. contributed new reagents/analytic tools; H.-M.B., L.S., S.-M.S., I.A., M.T., M.M., M.B., G.M.L., X.P., L.A., L.A.N., B.K., O.T.F., and O.T.K. analyzed data; and O.T.F. and O.T.K. wrote the paper.The authors declare no conflict of interest.This article is a PNAS Direct Submission.This article contains supporting information online at www.pnas.org/lookup/suppl/doi:10.1073/pnas.1613635114/-/DCSupplemental.